An intronic ncRNA-dependent regulation of SORL1 expression affecting Aβ formation is upregulated in post-mortem Alzheimer's disease brain samples - Eleonora Ciarlo; Sara Massone; Ilaria Penna; Mario Nizzari; Arianna Gigoni; Giorgio Dieci; Claudio Russo; Tullio Florio; Ranieri Cancedda; Aldo Pagano (The Company of Biologists, 2013)
SUMMARY Recent studies indicated that sortilin-related receptor 1 (SORL1) is a risk gene for late-onset Alzheimer's disease (AD), although its role in the aetiology and/or progression of this disorder is not fully understood. Here, we report the finding of a non-coding (nc) RNA (hereafter referred to as 51A) that maps in antisense configuration to intron 1 of the SORL1 gene. 51A expression drives a splicing shift of SORL1 from the synthesis of the canonical long protein variant A to an alternatively spliced protein form. This process, resulting in a decreased synthesis of SORL1 variant A, is associated with impaired processing of amyloid precursor protein (APP), leading to increased Aβ formation. Interestingly, we found that 51A is expressed in human brains, being frequently upregulated in cerebral cortices from individuals with Alzheimer's disease. Altogether, these findings document a novel ncRNA-dependent regulatory pathway that might have relevant implications in neurodegeneration.